Neuropathies in runners - Peck, E.; Finnoff, J. T. (Clinics in Sports Medicine, 2010)
Nerve entrapment represents an uncommon but important cause of lower limb pain among runners. This article reviews the diagnosis and management of several nerve entrapment syndromes that may be encountered among runners, but clinicians must be aware that any peripheral nerve may be affected. Successful diagnosis and management are predicated on several underlying principles: (1) maintain a high index of suspicion for neurologic syndromes, (2) recognize common presentations of neuropathic pain, (3) perform a meticulous physical examination, including postexercise examination when necessary, (4) consider a broad differential diagnosis (neurologic and nonneurologic), (5) use diagnostic testing appropriately, and (6) make rational clinical decisions, including referral for second opinion when indicated. A thorough knowledge of neuroanatomy and running biomechanics allows the clinician to successfully apply these principles to almost all clinical scenarios.